Barbárie e memória em Michel Laub: uma leitura da obra Diário da Queda - Ribeiro, Sileyr dos Santos (2022)
ABSTRACTA significant part of contemporary Brazilian literary production invests in the fictionalization of traumatic historical events (genocides, military dictatorships, etc.) in a critical perspective, intervening in the debate on the thematic clipping